Diseño de un modelo de gestión del talento humano por competencias para la florícola “Azeri Flowers” del cantón Pujilí de la provincia de Cotopaxi - Guachalá Lagla, Rita Elizabeth (2014)
The made study topic to consist on creating alternatives that contribute to the growth and development of the Floriculture Enterprises which there are in our country, since themselves count with necessary resources what can be exploited of the best manner, for this reason we see to involve in offering a solution to the problematic which has the organizations in the creation of a Department from Human Talent in the Floriculture "AZERI FLOWERS" into Pujilí Canton.